Not everyone is engaged: An innovative approach to measure engagement levels on the labor market - Carole Chartouni; Robert Holzmann; Gustavo N. Paez (IZA Journal of Labor Policy, 2020)
In this paper, we analyze the Individuals' level of engagement on the labor market and the engagement heterogeneity across individuals in matters of labor market outcomes and the effectiveness of policy interventions. Emerging economies with highly segmented and distorted labor markets typically exhibit strong heterogeneity in labor market engagement. This paper develops an innovative index that measures individuals' labor market engagement across three dimensions (preferences, intensity, and barriers) and across three labor market categories (employed, unemployed, and out-of-labor force) based on a recent special labor market survey in the Kingdom of Saudi Arabia (KSA). Clustering individuals with similar engagement levels permit more effective targeting of labor market interventions. Findings confirm the strong heterogeneity of labor market engagement in the KSA and the index's usefulness in the construction of differentiated policies across these clusters.
Keywords: C38; C43; J08; 330; labor engagement; labor barriers; labor preferences; latent variables